Patient, Practice, and Organizational Factors Associated With Early Mobility Performance in Critically Ill Adults. - Krupp, Anna E.; Tan, Alai; Vasilevskis, Eduard E.; Mion, Lorraine C.; Pun, Brenda T.; Brockman, Audrey; Hetland, Breanna; Ely, E. Wesley; Balas, Michele C. (American Journal of Critical Care, 2024)
Background: Adoption of early mobility interventions into intensive care unit (ICU) practice has been slow and varied. Objectives: To examine factors associated with early mobility performance in critically ill adults and evaluate factors' effects on predicting next-day early mobility performance. Methods: A secondary analysis of 66 ICUs' data from patients admitted for at least 24 hours. Mixed-effects logistic regression modeling was done, with area under the receiver operating characteristic curve (AUC) calculated. Results: In 12 489 patients, factors independently associated with higher odds of next-day mobility included significant pain (adjusted odds ratio [AOR], 1.16; 95% CI, 1.09–1.23), documented sedation target (AOR, 1.09; 95% CI, 1.01–1.18), performance of spontaneous awakening trials (AOR, 1.77; 95% CI, 1.59–1.96), spontaneous breathing trials (AOR, 2.35; 95% CI, 2.14–2.58), mobility safety screening (AOR, 2.26; 95% CI, 2.04–2.49), and prior-day physical/occupational therapy (AOR, 1.44; 95% CI, 1.30–1.59). Factors independently associated with lower odds of next-day mobility included deep sedation (AOR, 0.44; 95% CI, 0.39–0.49), delirium (AOR, 0.63; 95% CI, 0.59–0.69), benzodiazepine administration (AOR, 0.85; 95% CI, 0.79–0.92), physical restraints (AOR, 0.74; 95% CI, 0.68–0.80), and mechanical ventilation (AOR, 0.73; 95% CI, 0.68–0.78). Black and Hispanic patients had lower odds of next-day mobility than other patients. Models incorporating patient, practice, and between-unit variations displayed high discriminant accuracy (AUC, 0.853) in predicting next-day early mobility performance. Conclusions: Collectively, several modifiable and nonmodifiable factors provide excellent prediction of next-day early mobility performance.